A needs assessment of palliative care education in neurology residency programs in Brazil - Tramonte, Maiara Silva; Carvalho, Ana Claudia Pires; Pinheiro, Mariana Soares; Lopes, Camila Galvão; Neves, Luciana Oliveira; Lopes, Laura Cardia Gomes (Arquivos de Neuro-Psiquiatria, 2025)
The importance of integrating palliative care (PC) competencies into the management of neurological diseases is increasingly acknowledged. The National Medical Residency Program Commission (NMRPC) mandates the inclusion of PC in the curricula of neurology residency programs (NRPs).To evaluate the implementation of PC training in NRPs across Brazil and to identify barriers to its effective integration.We conducted a cross-sectional study using an anonymous online survey distributed to all NRP directors in Brazil through the Brazilian Academy of Neurology (BAN). The survey, approved by the institutional ethics committee, comprised 19 questions assessing PC training in NRPs. The responses were analyzed descriptively using IBM SPSS Statistics for Windows (IBM Corp.) software, version 26.0.The survey achieved a 32% (29 programs) response rate. Of the respondents, 82.8% (24 programs) reported the presence of an institutional PC team, and 75.9% (22 programs) incorporated PC training into their programs. However, only 1 neurology faculty member had formal PC training, and 37% of the directors expressed dissatisfaction with the quality of PC education. Key barriers included limited faculty availability (72.4%), lack of PC expertise (69%), and insufficient teaching time (58.6%).Palliative care training in Brazilian NRPs lacks consistency and systematic implementation. There is an urgent need for enhanced faculty training and strategic interventions to address structural and curricular barriers to improve PC education.
Keywords: Education, Medical; Internship and Residency; Neurology; Palliative Care